Enhancing Scientific Literacy in the Undergraduate Cell Biology Laboratory Classroom - Hadiya Woodham (American Society for Microbiology, 2016)
This paper describes the implementation of the Scientific Literacy in Cell Biology (SLCB) curriculum in an undergraduate biology laboratory course. The SLCB curriculum incorporated the reading and discussion of primary literature into hands-on and collaborative practical experiences. It was implemented in five stages over an 11-week period, during which students were also introduced to the theory and practice of common cell biology techniques. We report on the effectiveness of the course, as measured by pre- and post-course survey data probing students’ content knowledge and their level of familiarity, confidence, and experience with different skills pertaining to analyzing (reading, interpreting, and discussing) primary literature. In the spring 2015 semester, 287 (72%) of the 396 students who were enrolled in the laboratory completed both the pre- and post-course survey. The average score on the content questions of the post-course survey was significantly higher (p < 0.0001) than the average score on the pre-course survey. Students reported that they gained greater familiarity, experience, and confidence in the skills that were measured. Our findings may aid in reforming higher-education science laboratory courses to better promote writing, reading, data processing, and presentation skills. Journal of Microbiology & Biology Education